Down-regulation of SOCS6: an unfavorable prognostic factor for gastrointestinal stromal tumor proven by survival analysis - Jun Ouyang; Tailai An; Yan Wang; Xiaofang Lu; Yawei Zhang; Xiaokun Wang; Xinhua Zhang; Changhua Zhang (BMC, 2021)
Abstract Background Many studies reporting that down-regulation of SOCS6 plays vital roles in promoting progression of malignant tumors have been published. The present study was performed to evaluate whether SOCS6 was significantly associated with prognosis of GIST patients. Methods Immunohistochemical staining was accomplished to evaluate the expression levels of SOCS6 among GIST patients. The impacts of SOCS6 expression on overall survival (OS) and recurrence-free survival (RFS) of GIST patients were assessed by Cox proportional hazard regression model analysis and Kaplan-Meier curve analysis. Results It was demonstrated that the expression level of SOCS6 was significantly associated with tumor size (P=0.001). Then according to Kaplan-Meier curve analysis, low expression of SOCS6 was significantly correlated with worse OS and RFS of GIST patients. Ultimately, it was revealed by Cox proportional regression model analysis that low expression of SOCS6 was an independent predictive factor for OS and RFS. Conclusions Low expression of SOCS6 was an independent prognostic factor for GIST, suggesting its potential as a novel biomarker predicting survival of GIST patients.